Determinisme Teknologi Informasi Komunikasi dalam Keluarga - Rahmat Hidayat (Pancanaka, 2021)
Information and communication technology (ICT) penetration in families is so fast, especially during the Covid-19 pandemic. This study aims to examine the determinism of ICT in the behavior of families that access information and communication in the family. The research method used literature study with qualitative descriptive data analysis. The starting point for the discussion on the comparison between the natural social conditions of the family and changes in the behavior patterns of using ICT. The results of the study show that; ICT changes the behavior of family members in carrying out its eight functions. There are two things that are part of the argument in this article, namely ICT determinism and lifestyle and changes to changes in the implementation of the eight family functions. The development of digital ICT has formed new patterns of behavior so that it needs to be jointly aware of the importance of digital literacy and the state must be present through anticipatory, regulatory and solution policies so that there are ICTs at home that support the implementation of eight family functions.